The Use Of Board Game In Vocabulary Learning For The Eleventh-Grade Students - Ina Daril Hanna; Rini Listyowati (Gudang Jurnal Multidisiplin Ilmu, 2025)
This qualitative descriptive study investigated the impact of using board games into English vocabulary instruction for eleventh-grade students at MA Miftahul Ulum Bettet. Data were collected through classroom observations, structured interviews with five students and the teacher, and document analysis (lesson plans, student reflections). Thematic analysis revealed that board games significantly enhanced student engagement and motivation, fostering collaborative learning and contextualized vocabulary acquisition. Students reported increased enjoyment and improved vocabulary retention compared to traditional methods. While challenges related to time management and instructional alignment were identified, the findings strongly suggest that board games offer a valuable and effective supplementary approach to vocabulary instruction, aligning with constructivist and experiential learning principles.